2017
DOI: 10.1097/md.0000000000009287
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous kyphoplasty versus posterior spinal fixation with vertebroplasty for treatment of Kümmell disease

Abstract: This is a retrospective case–control study.The aim of this study was to compare the surgical results of percutaneous kyphoplasty (KP) and posterior spinal fixation with vertebroplasty (PSF+VP) for treatment of Kümmell disease (KD).KD is rare form of post-traumatic delayed avascular necrosis of the vertebral body. It is reported that KP is an effect measure for treatment of KD. Some studies have recommended posterior spinal fixation with vertebroplasty for KD.A total of 100 patients with KD who underwent spinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…After filling the fissures in the vertebral body with bone cement, the height and kyphosis deformity of the vertebral body were partially restored and corrected, and the abnormal activity of the injuried vertebral body was eliminated, which was an important reason for pain relief [11]. Previous studies have found that both PVP and PKP can effectively relieve the lower back pain of Kümmell's disease, achieve satisfactory clinical effect, and at the same time partially restore the height of the vertebra and correct the kyphosis [11,[21][22][23][24][25][26][27][28]. During spinal flexion and extension, due to the presence of IVC and the formation of false joints, the injured vertebra of Kümmell's disease can stretch and expand, which can widen the fractured vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…After filling the fissures in the vertebral body with bone cement, the height and kyphosis deformity of the vertebral body were partially restored and corrected, and the abnormal activity of the injuried vertebral body was eliminated, which was an important reason for pain relief [11]. Previous studies have found that both PVP and PKP can effectively relieve the lower back pain of Kümmell's disease, achieve satisfactory clinical effect, and at the same time partially restore the height of the vertebra and correct the kyphosis [11,[21][22][23][24][25][26][27][28]. During spinal flexion and extension, due to the presence of IVC and the formation of false joints, the injured vertebra of Kümmell's disease can stretch and expand, which can widen the fractured vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…After filling the fissures in the vertebral body with bone cement, the height and kyphosis deformity of the vertebral body were partially restored and corrected, and the abnormal activity of the injuried vertebral body was eliminated, which was an important reason for pain relief [11]. Previous studies have found that both PVP and PKP can effectively relieve the lower back pain of Kümmell's disease, achieve satisfactory clinical effect, and partially restore the height of the vertebra and correct the kyphosis [11,[22][23][24][25][26][27][28][29]. During spinal flexion and extension, due to the presence of IVC and the formation of pseudojoint, the injured vertebra of Kümmell's disease can stretch and expand, which can widen the fractured vertebral body.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some scholars intended to apply short or long segmental xation combined with vertebroplasty to avoid bone cement displacement. However, compared with using the bone cement alone, it has the disadvantages of large surgical trauma, loss of spinal mobility and high cost [3,36].…”
Section: Discussionmentioning
confidence: 99%